DAMPAK KEDISIPLINAN DAN MOTIVASI KERJA TERHADAP KINERJA ASN DI PEMERINTAH KABUPATEN GUNUNG KIDUL - Risma Nur Avita; Soffy Balgies; Achmad Willyansyah Ahyaturraja (Fakultas Psikologi Universitas Wijaya Putra, 2021)
ASN is a state apparatus in charge of implementing all existing policy steps within government agencies. The functions of the ASN or State Civil Apparatus include: as an implementer of public policy, as a public service in society, as well as as an adhesive and unifier of the nation. However, in carrying out their duties, civil servants were still found violating their work discipline. So, the application of work discipline in agencies needs to be considered. Because work discipline has a significant influence on employee performance. Work discipline is a process of assessing or correcting and giving punishment to subordinates for violating a rule or procedure. The application of work discipline includes imposing sanctions for those who break discipline. In addition, work motivation also affects employee performance in carrying out predetermined tasks. Where motivation is a factor that can support a person in carrying out a certain activity or activity, where every activity carried out by someone must have a stimulus. This includes giving rewards to employees who have reached a predetermined limit, providing adequate facilities, providing social security, etc.